Comparison between results of different methods of determination of water surface elevation in tidal rivers and determination of the best method - Adib, Arash; Banetamem, Ali; Navaseri, Abbas (International Journal of Integrated Engineering, 2017)
Fluvial flows in the upstream of tidal rivers and tidal surges in the downstream of them are governing factors in tidal rivers. Hydraulic routing is a very difficult problem in tidal rivers.In this research, three methods are developed for determination of water surface elevation in tidal rivers. Results of these methods are compared to results of conventional method.These methods are applied for the Karun River. Selected reach locates between Ahvaz in the upstream and there branches junction of Khoramshar in the downstream.At the first, a numerical model is developed and envelopes of curves are extracted by results of this model. Then, structural regression relations which are governing on envelopes of curves are determined. In the other hand, a neural network is trained by results of numerical model. At the end, results of envelopes of curves method, structural regression relations method and neural network method are compared.Â